Company Size and Price-Earnings Ratio as A Signal in Influencing Firm Value Moderated by Investment Decisions - Nurjanah, Rina; Yahya, Adibah; Wulandari, Anna (Jurnal Ekonomi Syariah Pelita Bangsa, 2024)
This study aims to examine the impact of firm size and price-earnings ratio on firm value, with investment decisions as a moderating variable, focusing on property and real estate companies listed on the Indonesia Stock Exchange from 2020 to 2023. The research employs a quantitative approach using panel data regression analysis. Financial data were collected from annual reports and financial statements of listed property and real estate companies. The study utilises E-Views software for data analysis, including descriptive statistics, correlation analysis, and moderated regression analysis. The findings reveal that firm size and price-earnings ratio positively and significantly influence firm value. However, investment decisions do not moderate the relationship between firm size or price-earnings ratio and firm value in the context of Indonesian property and real estate companies during the studied period. The study is limited to a specific sector and time frame, which may affect the generalizability of results. Additionally, secondary data may not capture all nuances of managerial decision-making processes. This research contributes to the body of corporate finance and strategic management knowledge by providing insights into the determinants of firm value in the Indonesian property and real estate sector.